2010
DOI: 10.1177/0009922810368558
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Risk Factors, and Complications Among Pediatric Patients With Pandemic Influenza A (H1N1)

Abstract: In this cohort, most children with confirmed H1N1 infection experience an uncomplicated viral illness. Nevertheless, underlying asthma and obesity may aggravate their clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 15 publications
1
29
1
2
Order By: Relevance
“…Among the 6 patients admitted to the ICU, 3 had lymphopenia similar to studies from India, California and Mexico [18,19,20,21,22]. In Mexico, the analysis of 18 deaths caused by H1N1 infection in previously healthy subjects revealed lymphopenia in 16% of them; apparently lymphopenia is an important risk factor and patients should be closely observed, especially those with underlying medical conditions.…”
Section: Discussionsupporting
confidence: 55%
“…Among the 6 patients admitted to the ICU, 3 had lymphopenia similar to studies from India, California and Mexico [18,19,20,21,22]. In Mexico, the analysis of 18 deaths caused by H1N1 infection in previously healthy subjects revealed lymphopenia in 16% of them; apparently lymphopenia is an important risk factor and patients should be closely observed, especially those with underlying medical conditions.…”
Section: Discussionsupporting
confidence: 55%
“…Underlying medical conditions including asthma and obesity have been reported in pediatric studies to be risk factors for morbidity or mortality 1,6 . In the present study, underlying medical conditions showed no statistical significance on either univariate or multivariate analysis.…”
Section: Discussioncontrasting
confidence: 74%
“…Basic demographic and clinical data including age, sex, length of hospitalization, fever duration, and underlying medical conditions, as well as vital signs (heart rate and respiratory rate at admission) were obtained from patient charts. Data such as underlying medical conditions, 1,6 and interval from symptom onset to oseltamivir treatment, 7 obtained from previous studies with important factors of morbidity of pH1N1 were also recorded. The underlying medical conditions considered to be established risk factors for severe influenza included chronic pulmonary disease including asthma, hemodynamically significant cardiac disease, hemoglobinopathy, immunosuppressive treatment, chronic renal dysfunction, chronic metabolic disorder, and neuromuscular disorder.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Several cross-sectional and cohort studies have suggested that obesity may contribute to respiratory complications in children. 1113 These findings provide important rationale for investigations of pediatric obesity outcomes. However, the findings may not be generalizable to acutely ill children, especially because unique short-term consequences may result from pediatric obesity.…”
mentioning
confidence: 93%